Central amygdala astrocyte plasticity underlies GABAergic dysregulation in ethanol dependence - Todd B. Nentwig; J. Daniel Obray; Anna Kruyer; Erik T. Wilkes; Dylan T. Vaughan; Michael D. Scofield; L. Judson Chandler (Translational Psychiatry)
Abstract Dependence is a hallmark of alcohol use disorder characterized by excessive alcohol intake and withdrawal symptoms. The central nucleus of the amygdala (CeA) is a key brain structure underlying the synaptic and behavioral consequences of ethanol dependence. While accumulating evidence suggests that astrocytes regulate synaptic transmission and behavior, there is a limited understanding of the role astrocytes play in ethanol dependence. The present study used a combination of viral labeling, super resolution confocal microscopy, 3D image analysis, and slice electrophysiology to determine the effects of chronic intermittent ethanol (CIE) exposure on astrocyte plasticity in the CeA. During withdrawal from CIE exposure, we observed increased GABA transmission, an upregulation in astrocytic GAT3 levels, and an increased proximity of astrocyte processes near CeA synapses. Furthermore, GAT3 levels and synaptic proximity were positively associated with voluntary ethanol drinking in dependent rats. Slice electrophysiology confirmed that the upregulation in astrocytic GAT3 levels was functional, as CIE exposure unmasked a GAT3-sensitive tonic GABA current in the CeA. A causal role for astrocytic GAT3 in ethanol dependence was assessed using viral-mediated GAT3 overexpression and knockdown approaches. However, GAT3 knockdown or overexpression had no effect on somatic withdrawal symptoms, dependence-escalated ethanol intake, aversion-resistant drinking, or post-dependent ethanol drinking in male or female rats. Moreover, intra-CeA pharmacological inhibition of GAT3 did not alter dependent ethanol drinking. Together, these findings indicate that ethanol dependence induces GABAergic dysregulation and astrocyte plasticity in the CeA. However, these changes in astrocytic GAT3 do not appear to be necessary for the drinking related phenotypes associated with dependence.